Just One-CLiQQ project: Stabilizing connectivity issue of 7-eleven’s CLiQQ kiosk - Gonzales, Ralph Raymond C. (Animo Repository, 2021)
The stability of the online payment connection of 7-Eleven plays a massive role in the retail performance of the company as we embrace technological innovation in service operations. CLiQQ Kiosks in 7-Eleven stores is a convenient way for customers to pay items, buy cell phone load, e-pins, pay bills, and add cash to their e-money. The project is significant in addressing customer complaints of "no connectivity," which have long-term effects of protecting the brand, retaining customer loyalty, and attracting potential ones.